LANGUAGE EXPERIENCE APPROACH (LEA) IN TEACHING READING COMPREHENSION: A CLASSROOM ACTION RESEARCH IN A PRIVATE UNIVERSITY IN INDONESIA - Wandansari, Tantri (2014)
The aims of this present research were investigating whether Language Experience Approach (LEA) can develop students' reading comprehension and finding out the most effective activities of LEA in developing the students' reading comprehension. Twenty one second-semester students of Accounting Department in one private university in Bandung were involved in this research. The method used in this research was collaborative action research. The researcher acted also as the English instructor and an assistant who took part from the beginning to the end of the research helped observe the teaching and learning process. The data were collected by using techniques of qualitative and quantitative data collection which included observation, interview, research diary and reading test. The qualitative data were analyzed through re-reading and describing the research diary, pre-research observation report, and field notes. The quantitative data were analyzed by comparing the gain score of the reading test in each cycle. The result indicated that LEA-based strategy can improve the students' reading comprehension with the following effective activities. First, in share and discuss experience stage, teacher determines what stimulus will be used to define the "experience". It can be a photo or an illustration. Second, in dictation stage, teacher divides the students into groups and each group verbally recreates the shared experience. The teacher then transcribes the student's words on the board in an organized way to create the text. Third, in read and revise stage, the class reads the story aloud and discusses it. In this stage, the teacher should make corrections of the students' grammatical errors. Fourth, in extension stage, as a follow-up activity, the teacher asks the students to find certain terms or English structures related to the materials and they write their own variations of the LEA story with a given structure. Fifth, in assessment stage, students are given a text and they are asked to answer the questions accompanying the text. Besides that, they should make a summary of the text with their own words. Those procedures were regarded as the most effective procedures in implementing LEA in this study. However, LEA can also be problematic in teaching reading. Second language learners with limited language proficiency will often dictate sentences with critical errors that would not be appropriate as a reading resource since these errors can be mistakenly taken for acceptable expressions. One of the possible alternatives is making partial correction of the fundamental errors by the teacher. By doing that, it can help to eliminate the problem with reinforcing inappropriate language structures.